Sebuah Analisis Kritik Sosial dalam Cerita Pendek Hikayah Mishriyyah Jiddan Karya Yusuf Idris (Kajian Sosiologi Sastra) - Najma Tanzila; Nezard An Naufal; Najwa Na'afilla Karimah; Eva Farhah (Jurnal Sathar, 2024)
This study analyzes social criticism in Yusuf Idris's short story Hikayah Mishriyyah Jiddan using a sociology of literature perspective. The focus of the research is to identify social criticism and its connection to the social reality of Egypt. The method used is descriptive qualitative, employing Karl Marx's theory of social criticism, which encompasses issues of economics, politics, culture, and morality. The findings reveal criticism of economic inequality, systemic corruption, cultural shifts eroding empathy, and moral degradation. This criticism is conveyed through the interaction between the taxi driver and the beggar, representing the social dynamics of Egyptian society. The short story not only presents a fictional narrative but also reflects social issues relevant to its time. This study affirms that literary works play a significant role as a medium of social criticism to raise public awareness.